Strategi Membangun Kerukunan Umat Beragama - Hamidah Hamidah (Wardah, 2016)
Abstract: The paradigm of freedom and religious tolerance in Islam contains teachings about human equality . On top of this equation can be formed brotherhood and friendship among religious followers in social life based on humanity for the realization of social order together. Therefor of humanity, Islam knows no exclusivism, and of the faith, Islam also does not recognize intolerance. Socially Islamic outline to the nation that is not allowed to argue with the followers of other religions, but in a polite way and ethically, and they can do good and be fair to other religious communities. Expansion of the actual interpretation of religious teachings and empirically with relevance with aspects of socio-economic realities, politics and culture is an effort of socialization and inculturation of religious values in the society and the nation, especially in the construction, so that religion can be played in development. And breadth of insight religion religious teachings will foster attitudes and views are open and inclusive to the problems of social and humanitarian mankind.